Identification of Ethnogenesis in the Communication and Adaptation Process of the Alor Community in the Sunda Culture Area - Adhi KUSUMA; Ahmad SIHABUDIN; Dewi WIDOWATI (International Journal of Environmental, Sustainability, and Social Science, 2023)
Facing a new environment, the differences in values, culture, norms, language styles, and social behavior between the Alor and Sundanese have created a space for ethnogenesis that is faced with being able to adapt to each other in interacting and coexisting. Through the formation of communication and the process of adaptation, it is the starting point for the Alor people to improve the quality of life in terms of education, economy, social, politics and culture. This article aims to reflect on the process of interaction, communication interaction patterns and the process of adaptation of the Alor people to the Sundanese based on the Anxiety/Uncertainty Management Theory approach. Descriptive qualitative method by prioritizing the post-positivist paradigm was used on six purposive sample informants which were taken based on the Snowball sampling technique. This study shows that interaction occurs as an interest in realizing a harmonious life through verbal and non-verbal communication interaction patterns according to Sundanese cultural characteristics and the reflection of the adaptation process carried out is seen from three dimensions, namely cognitive, affective, and behavioral. Alor people learn language styles, values, manners, social behavior, prioritize indigenous culture, put aside personal culture, and promote good socialization by the Alor people towards the Sundanese.